2023
DOI: 10.3390/ijerph20085485
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Fitness for Identifying Low Physical Function in Older Women

Abstract: Aims: This cross-sectional study aimed to analyze the relevance of musculoskeletal fitness for identifying low physical functioning in community-dwelling older women. Methods: Sixty-six older women (73.62 ± 8.23 yrs old) performed a musculoskeletal fitness assessment of the upper and lower limbs. A handheld dynamometer was used to evaluate upper-limb muscle strength through a handgrip (HG) test. Lower-limb power and force were assessed from a two-leg countermovement vertical jump (VJ) on a ground reaction forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…On the other hand, the CMJ exhibited more significant correlations with functional and cardiorespiratory tests. Previous studies have observed significant correlations between relative power and maximum vertical jump velocity ( Parsons et al, 2020 ; Abreu et al, 2023 ). Similar to the current study, previous work by Winger et al reported that relative power in vertical jump and speed at maximum power showed associations twice as strong compared to HG strength ( Winger et al, 2020 ).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…On the other hand, the CMJ exhibited more significant correlations with functional and cardiorespiratory tests. Previous studies have observed significant correlations between relative power and maximum vertical jump velocity ( Parsons et al, 2020 ; Abreu et al, 2023 ). Similar to the current study, previous work by Winger et al reported that relative power in vertical jump and speed at maximum power showed associations twice as strong compared to HG strength ( Winger et al, 2020 ).…”
Section: Discussionmentioning
confidence: 87%
“…Concerning TUG, consistent with our study, it correlated significantly with squats, walking speed, SPPB, and the 30-s sit-to-stand test ( Santos et al, 2022 ), exhibiting higher correlations compared to HG ( Staples et al, 2020 ). Several studies emphasize that lower limb muscle power might be a more relevant marker for aging compared to HG and muscle mass ( Runge et al, 2004 ; Parsons et al, 2020 ; Abreu et al, 2023 ). Power and speed could be more crucial factors in preventing functional loss in older individuals compared to muscle strength ( Winger et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations